ChemInform Abstract: Novel Features of Multiferroic and Magnetoelectric Ferrites and Chromites Exhibiting Magnetically Driven Ferroelectricity. Issue 27 (8th July 2014) - Saha, Rana; Sundaresan, A.; Rao, C. N. R.
Abstract Review: 86 refs.